Post-Keynesian economics in Germany since the 1970s: A detailed mapping of the landscape - Eckhard Hein (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2025)
This paper maps the intellectual and institutional landscape of post-Keynesian economics in Germany since the 1970s. It reviews the contributions of academics based in Germany, irrespective of their nationality, to post-Keynesian economics viewed from a broad tent perspective and to the different strands within this broad-tent post-Keynesian economics. The focus is on the contributions and it is not implied that the authors consider themselves to be post-Keynesians or to adhere to some of the different strands of post-Keynesian economics. Based on the assessment of the contributions, some light is shed on the institutional development of post-Keynesian research and teaching in German higher education, on academic associations, networks, and institutes, as well as on academic journals and publishers open to post-Keynesian research in Germany. It is concluded that the generational transition, associated with the retirement of those researchers who got into the university sector in the 1970s and 1980s, has been managed with relative success and post-Keynesian economics has been consolidated, albeit at a low level, and that it remains an embattled minority in Germany.
Keywords: B22; B25; E12; 330; post-Keynesian economics; Germany; history of economics